2008
DOI: 10.1159/000129677
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Classic Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency Can Achieve Their Target Height: The Leipzig Experience

Abstract: Background: Despite treatment, the mean final height (FH) of patients with classic congenital adrenal hyperplasia (CAH) is below the mean height of a normal population. Aims:To show that CAH patients can achieve their target height (TH), 39 adult subjects, whose therapy had started in infancy, were studied in a retrospective analysis. All height SDS were corrected so that they related to TH SDS. Patients: Group 1: patients born before 1975 (n = 13) had received prednisolone, at doses equivalent to hydrocortiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 72 publications
3
22
0
3
Order By: Relevance
“…Genital stages G2 and G3 occurred earlier, but G4 occurred later in boys, and stages B2 and B4 occurred later in girls, respectively. This is probably driven by an advanced BA as reported variously in CAH, and more pronounced so in boys than in girls [1,4,23,29,30]. We speculate that earlier pubarche before gonadarche in girls and SW boys might be due to an incomplete androgen suppression in order to avoid glucocorticoid overtreatment.…”
Section: Discussionmentioning
confidence: 53%
“…Genital stages G2 and G3 occurred earlier, but G4 occurred later in boys, and stages B2 and B4 occurred later in girls, respectively. This is probably driven by an advanced BA as reported variously in CAH, and more pronounced so in boys than in girls [1,4,23,29,30]. We speculate that earlier pubarche before gonadarche in girls and SW boys might be due to an incomplete androgen suppression in order to avoid glucocorticoid overtreatment.…”
Section: Discussionmentioning
confidence: 53%
“…It is believed that treatment interference is a major cause, in addition to the influence of excessive androgen production that occurs despite the best possible control. Recent data point out to the harm ful impact of glucocorticoid treatment in FH outcomes (11), and other reports suggest better outcomes after the use of lower HC doses (12)(13). Alternative treatments, such as the use of growth hormone associated to puberty inhibitors, in addition to anti-estrogen therapy, were used in an attempt to improve height prognosis in these patients (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a group of patients who initiated treatment early reached their TH. There is now some evidence that, with appropriate clinical management, children can achieve their genetic potential (2,13,21).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that mineralocorticoid therapy in salt-wasting CAH improves linear growth and may allow for lower doses of glucocorticoids [56]. In a German study [34], a retrospective analysis of 39 adult patients with CAH found that a reduced daily dose of glucocorticoid was possible with the addition of daily fludrocortisone and was associated with improved FH. The authors proposed using a daily fludrocortisone dose of 110 mcg/m 2 from preschool age onwards and suggested that this would result in a reduced mean hydrocortisone dose of approximately 13 mg/m 2 /day in their patients.…”
Section: Mineralocorticoid and Salt Replacement—important Influencmentioning
confidence: 99%